Análisis, diseño, desarrollo e implementación de un sistema Web de control de historias y citas médicas para el Departamento médico de la UPS Campus Sur - Llano Jiménez, Alejandro Andrés (2018)
This project will use all knowledge that has been acquired throughout the university career and it consists of a web system for automation of care processes in the medical center of the university's south campus, because it handles information of patients in a traditional way by physical documents, so the process is slow, there is also the risk of information loss or that inaccurate information is recorded, which will be controlled by the system showing a faster and efficient attention for patients. The users will be an integral part of the system therefore the success will depend on its correct use in this way will be achieved that the control system be integrated efficiently and contribute to improve the quality of care reflecting a remarkable satisfaction on the part of doctors and patients.